5PSQ-122 Contribution of the monitoring of quality indicators on improving paediatric's hospital pharmacy's performance. (2nd March 2018) - Attjioui, H; Rahali, Y; Cheikh, A; Aliat, Z; Berbouchi, L el; Mefetah, H; Bouatia, M
Abstract : Background: The implementation of quality indicators within the hospital pharmacy have a fundamental role in the creation of its value. It contributes significantly to the achievement of the strategic goals of the structure and allows managers to measure and manage in a better way their performance. Purpose: The aim is to explore the hospital pharmacy practice in terms of the use of quality indicators and their relation to performance. Material and methods: We have measured the internal process performance indicators and the support process efficiency indicators over the last 3 years, by measuring the customer satisfaction rate and calculating the rate of breakage, deterioration, expiry of drugs and medical devices and the rate of reactivity of corrective actions, whose formula has been previously determined in advance. The data needed for this calculation were collected using the nonconformity reporting sheets and the pharmacy database as well as a questionnaire sent to the hospital's clinical departments. The calculated results were compared to the analysis threshold set for each indicator. Results: Measuring the internal process indicators over the years 2015, 2016 and the first half of 2017 showed that the strategic objectives set for all the performance indicators have been achieved for the 3 years except breaking indicators of drugs has increased in August of 2016 by a rate of 13%, which exceeds the normal threshold: this is a breakdown of 17 products and an efficiency rate of immediate actions that has decreased slightly to 68.8% compared to the threshold (>70%) during the month of December of the same year. These non-conformities have pushed the pharmacy team to review the shortcomings and take corrective measures. And regarding the effectiveness of process indicators support, a significant improvement was observed in 2016 compared to the previous year. Conclusion: We can say that performance is positively associated with quality indicators That allow us to achieve fixed goals and objectives, and to make immediate or long-term decisions in order to improve and increase the performance of the concerned structure. Reference and/or Acknowledgements: 1. Meftah H, et al. Contribution of hospital pharmacy ISO certification 9001 on improving performance indicators: Experience of pharmacy of a paediatric hospital. Eur J Hosp Pharm 2017. No conflict of interest